Trigo br 38-a new wheat cultivar for Rio Grande do Sul - Rosa, Ottoni de Sousa; Barcellos, Amarilis Labes; Zanatta, Ana Christina Albuquerque; Pretes, Ariano Moraes; Tomm, Gilberto Omar; de sousa, Cantídio Nicolau Alves; Gomes, Edar Peixoto; Moreira, João Carlos Soares; Sartori, João Francisco; Caetano, Vanderlei da Rosa (Pesquisa Agropecuaria Brasileira, 1993)
A new wheat cultivar, named Trigo BR 38, developed by EMBRAPA at the Centro Nacional de Pesquisa de Trigo, in Passo Fundo, RS, was released to the farmers of Rio Grande do Sul, Brazil, in 1990. It is characterized for its average height (90-95 cm), high yielding potential, and resistance to some diseases. In relation to yield, considering the mean of 49 experiments carried out from 1987 to 1989, Trigo BR 38 overyielded the best check cultivar by 8%. As to its resistance to mildew, caused by Erysiphe graminis tritici, as well as to stem rust, caused by Puccinia graminis tritici it has the advantage that the sources of resistance used were not yet introduced into commercial cultivars in Brazil and in Rio Grande do Sul, respectively.
Keywords: resistance to diseases; mildew; Erysiphe graminis tritici; stem rust and Puccinia graminis tritici